The Impact of Technostress on Malaysia Educator’s Performance in the Age of Covid-19 - Ismail, Nur Azira; Mohd Adi, Mohd Nazir (Research in Management of Technology and Business, 2022)
Covid-19 pandemic has an impact on many industries including education sector particularly higher institutions. The process of teaching and learning process must keep ongoing despite of the closing of the universities and college. All classes has been shifted to online platform from the face to face classroom. This rapid and wide-ranging change of online teaching approaches is closely related to stress levels of educators face. This is known as a technostress which is stress caused by rapid change in technology thus could impact educator’s performance. This study aims to examine the relationship between technostress creators namely techno-overload, techno-complexity and techno-insecurity on the educator’s performance during Covid 19. This study was a cross-sectional survey research design and implementing quantitative method by distributing questionnaires to educators who conduct online teaching. A total of 159 educators from private college and university in Johor Bahru were selected as sample using purposive sampling technique. The collection of data has been analyzed using SPSS software. The analysis used in the study was descriptive analysis and correlation analysis. The results of this study shown that there was a significant relationship between techno-overload, techno-complexity and techno-insecurity on performance among educators from private college and university in Johor Bahru during Covid 19. Hence, this study is important to enhance the understanding of educators on technostress creators and to provide them to come out with the strategies for effective use of ICT integration in teaching performance during Covid 19 outbreak.